Interplay between reaction and diffusion processes in governing the dynamics of virus infections. (14th November 2018) - Bocharov, G.; Meyerhans, A.; Bessonov, N.; Trofimchuk, S.; Volpert, V.
Highlights: A delay reaction-diffusion model describes the virus infection dynamics in tissue. The infection dose, delays and diffusion rates determine the infection fate. Infection can be eliminated or persist in a spatially uniform or oscillatory mode. Slow immune cell motility results in immune cell exhaustion. Abstract: Spreading of viral infection in the tissues such as lymph nodes or spleen depends on virus multiplication in the host cells, their transport and on the immune response. Reaction-diffusion systems of equations with delays in cell proliferation and death by apoptosis represent an appropriate model to study this process. The properties of the cells of the immune system and the initial viral load determine the spatiotemporal regimes of infection spreading. Infection can be completely eliminated or it can persist at some level together with a certain chronic immune response in a spatially uniform or oscillatory mode. Finally, the immune cells can be completely exhausted leading to a high viral load persistence in the tissue. It has been found experimentally, that virus proteins can affect the immune cell migration. Our study shows that both the motility of immune cells and the virus infection spreading represented by the diffusion rate coefficients are relevant control parameters determining the fate of virus-host interaction.